COVID-19 from a techno-educational perspective through markerspaces - Moreno Martínez, Noelia Margarita; Morales Cevallos, María Belén (IJERI: International Journal of Educational Research and Innovation, 2020)
In the face of the health emergency that occurred worldwide due to the COVID-19 pandemic, in the educational field there is a need to design teaching materials to make this phenomenon known to students and the best ways to act promoting solidarity attitudes, joint community work and a social conscience. To do this, this work presents augmented reality tools, 3D modeling and 3D printing to promote the study, analysis and understanding of the nature, structure, composition and origin of the virus, the factors that trigger the infections, the symptoms presented by the infected subject, and prevention and safety measures. From an innovative approach, teachers of the digital age must have training from the pedagogical and instrumental and technological point of view to successfully undertake their teaching work aimed at facilitating the acquisition and construction of knowledge by their students. For this, the support, the material used as a mediator, in this case the emerging technologies to promote online learning from a connectivist perspective, considering the collaborative and creative philosophy of makerspaces, is considered of special importance.